Brachial Plexus Schwannoma: Case Report and Literature Review - Mateus de Sousa Rodrigues; Gabriel Albuquerque Leite Cavalcante; Camila Maciel Martins Coelho; Victor de Paula Fonseca; Déborah Emmily de Carvalho; Pedro Lucas Negromonte Guerra; Mayle Gomes Ferreira de Araújo; Lívio Pereira de Macêdo; Everton Felipe Do Vale Araujo; Fernando Henrique Morais de Souza; Eduardo Vieira de Carvalho; Nivaldo Sena de Almeida; et al. (Brazilian Neurosurgery)
Schwannomas are mostly benign and solitary tumors that originate from Schwann cells. Macroscopically, they appear as rounded masses with a smooth surface. Schwannomas rarely affect the brachial plexus, accounting for approximately 5% of all cases of schwannomas, presenting a challenge for surgeons. The objective of this article is to describe a case report of a brachial plexus schwannoma in a hospital located in the Northeast of Brazil. A 49-year-old male patient presented pain resulting from the appearance of a left anterior cervical bulging with progressive growth. On physical examination, he had a Medical Research Council (MRC) score of 3 in left arm abduction and paresthesia in the left lateral forearm and arm. On magnetic resonance imaging (MRI), the lesion arises from the C4-C5 junction, measuring 5.9 × 5.4 × 5.5 cm, and the electroneuromyography showed chronic pre-ganglionic involvement of C5 to C7 bilaterally. A left cervicotomy was performed with a horizontal incision at the level of the laryngeal eminence. Brachial plexus lesions with progressive growth tend to be managed surgically. This diagnosis hypothesis should be considered in patients presenting progressive neck bulging in inspection during physical examination. This is an easy and cheap method of suspicion that can be used by health professionals.